2022
DOI: 10.1002/acm2.13523
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance for on‐table adaptive magnetic resonance guided radiation therapy: A software tool to complement secondary dose calculation and failure modes discovered in clinical routine

Abstract: Online adaption of treatment plans on a magnetic resonance (MR)‐Linac enables the daily creation of new (adapted) treatment plans using current anatomical information of the patient as seen on MR images. Plan quality assurance (QA) relies on a secondary dose calculation (SDC) that is required because a pretreatment measurement is impossible during the adaptive workflow. However, failure mode and effect analysis of the adaptive planning process shows a large number of error sources, and not all of them are cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…It was designed using LimeSurvey (LimeSurvey GmbH, Hamburg, Germany) containing 18 questions in multiplechoice style. Self-assessment concerning knowledge on RM was answered using a 5-point Likert scale: very good (1)-good (2)-satisfying (3)-bad (4)-very bad (5). Process steps as mentioned in the questionnaire were aligned to the WHO radiotherapy risk profile [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was designed using LimeSurvey (LimeSurvey GmbH, Hamburg, Germany) containing 18 questions in multiplechoice style. Self-assessment concerning knowledge on RM was answered using a 5-point Likert scale: very good (1)-good (2)-satisfying (3)-bad (4)-very bad (5). Process steps as mentioned in the questionnaire were aligned to the WHO radiotherapy risk profile [3].…”
Section: Methodsmentioning
confidence: 99%
“…Radiation oncology (RO) plays a vital role in cancer management with almost half of all patients undergoing radiation therapy (RT) during their course of disease [1]. Modern leading to a devastating impact in terms of side-effects and therapy success [2][3][4][5]. In recent years, several organizations have focused on patient safety during RT, providing recommendations for radiation oncology professionals [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Simpler non-dosimetric solutions have also been proposed to check irregularities during the plan adaptation and patient model creation processes including contour analysis, electron density map examinations, and fluence modulation complexity controls. In a recent study [33] , irregularities were found in 9 out 362 adapted fractions.…”
Section: Discussionmentioning
confidence: 86%
“…This kind of contouring issue is not easily caught by the secondary absorbed-dose calculation QA because contour and electron density are direct inputs to it, indicating the necessity to develop additional automated plan check tools to identify the issues associated with contouring and electron density mapping. Based on the potential risks identified in the FMEA of the adaptive planning process, several in-house tools for automated contour analysis, electron density examination, and additional plan checks have been reported as complementary plan QA to the secondary absorbed-dose calculation (Cai et al , 2018; Rippke et al , 2022).…”
Section: Online Adaptive Mrigrtmentioning
confidence: 99%
“…Mitigation strategies such as standardized workflow, clearly-defined protocols, and checklists to ensure protocol adherence were implemented to minimize all the high risks that were classified based on the combination of probability and severity levels to an acceptable level (Klüter et al, 2021). Contouring and electron density assignment were also reported to be the highest risk priority categories by different institutions (Garcia Schüler et al, 2021;Rippke et al, 2022). The quality of the contour directly impacts the quality of the treatment plan as shown by an example in Fig.…”
Section: Quality Assurance For Mrigrt-adaptive Radiotherapymentioning
confidence: 99%